Validation of Taiwanophodes minor Hlaváč, 2003 (Coleoptera: Staphylinidae: Pselaphinae) - Hlaváč, Peter (Zootaxa, 2020)
In my 2003 paper (Hlaváč 2003) dealing with a revision of the Pselaphodes complex of genera, I neglected to explicitly designate a depository of the holotype of Taiwanophodes minor Hlaváč sp. n. Under ICZN (1999): Article 16.4.2 this omission invalided its description and the species name. I herein rectify this problem.